An ontogenic study of adrenomedullin gene expression in the rat lung, adrenal, kidney, and heart - Wong, P. F.; O, W. S.; Tang, F. (Endocrine, 2012)
In this study, the gene expression of adrenomedullin ( Adm ) in the peripheral tissues which include lung, adrenal, kidney, and heart during development was investigated in the rat. The preproadrenomedullin ( preproAdm ) mRNA and mRNAs of its related receptor components, calcitonin receptor-like receptor ( Crlr ), and receptor activity-modifying proteins ( Ramp1 , 2 and 3 ) of the lung, adrenal, kidney, and heart were measured by real-time RT-PCR and the ADM peptide measured by radioimmunoassay in 1-, 7-, 21-day-old rats and the adult rats. From day 1 to 21, preproAdm mRNA levels increased with age in the lung, the kidney, and the heart but decreased with age in the adrenal. ADM levels, however, increased with age in the lung but decreased with age in the kidney, the adrenal, and the heart. The preproAdm levels in the lung, in the kidney, and in the adrenal all increased in the adult rat. ADM peptide levels, however, decreased in the adult rat. Crlr and Ramp2 gene expression increased with age in the lung, in the kidney, and in the heart but decreased with age in the adrenal in the prepubertal rats. The results indicate that the levels of preproAdm mRNA, ADM peptide and its receptor component mRNAs in different tissues followed different patterns of changes during development.